(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: For assessing the sex of unidentified or skeletonized individuals, the tooth crown diameters are a good and reliable source amongst the other clinical markers. Aim and Objectives: To check the accuracy and reliability of Mandibular Canine Index (MCI) in sex determination among Saudi subpopulation using 3D Cone Beam Computerized Tomography (CBCT) images. An additional objective is to establish the norm of Standard MCI. Methodology: A total of 400 CBCT images were studied for the measurements of mesio-distal width (MDW) and inter-canine distance (ICD) of mandibular canines. Then, the observed and Standard MCI were calculated that was statistically determined by receiver operating characteristic (ROC) analysis. Results: Left canine showed greater sexual dimorphism. The Standard MCI was calculated as 0.239 (right mandibular canine) and 0.241 (left mandibular canine). The ability to determine gender correctly using Standard MCI (right mandibular canine) method was estimated to be 49% among males and 46.5% among females. The accuracy of the method, when applied to the combined data, was 47.8%. Conclusion: MCI and the variables that allow MCI quantification were shown to distinguish the groups, in terms of average, suggesting the possibility that canine-related measurements may be used for sex discrimination.